Preservation of cortical histamine H3 receptors in ischemic vascular and mixed dementias. - Sheng, Y; Lee, J; Medhurst, A; Wilcock, G; Esiri, M; Wong, P; Chen, C; Lai, M (2012)
AIM: Histamine H(3) receptor antagonists have been proposed as a novel therapeutic approach for the symptomatic treatment of Alzheimer's disease (AD). However, it is unclear whether there is a neurochemical basis for extending their potential use in vascular and mixed dementias. In this study, we measured cortical H(3) receptors in patients with subcortical ischemic vascular dementia (SIVD) and mixed SIVD/AD (MIX). MATERIALS AND METHODS: Radioligand binding assays using [(3)H]GSK189254 were used to measure H(3) receptors in the postmortem frontal cortex, anterior cingulate gyrus and hippocampus of a cohort of longitudinally assessed SIVD, MIX and age-matched controls. RESULTS: H(3) receptor levels were unchanged in SIVD and MIX in all areas studied. Furthermore, frontal H(3) receptor densities negatively correlated with predeath assessment of cognition using Mini-Mental State Examination (MMSE) scores. CONCLUSION: Our data suggest that H(3) receptors are preserved in SIVD and MIX, thus supporting further assessments of H(3) antagonists as potential therapeutics in these dementias.